Polystyrene microplastics arrest skeletal growth in puberty through accelerating osteoblast senescence. (1st April 2023) - Pan, Chun; Wu, Yin; Hu, Sihan; Li, Ke; Liu, Xiangyu; Shi, Yu; Lin, Wenzheng; Wang, Xinglong; Shi, Yujie; Xu, Zhuobin; Wang, Huihui; Chen, Hao
Abstract: Polystyrene microplastics (PS-MPs) have attracted worldwide attention to their massive accumulation in terrestrial and aquatic ecosystems. It has been demonstrated that MPs are easily to accumulate in organs and exert toxic effects. However, their exposure risk to the skeleton remains unknown. In this study, we observed PS-MPs accumulation in both the long bones and axial bones, leading to reduced body length, as well as femur and tibia length. PS-MPs treated mice exhibited redundant skeletal growth and impaired trabecular bone micro-architecture, which is due to the suppressed osteogenic ability as the number of osteoblasts decreased significantly in PS-MPs treated mice . In histological analysis, we observed the accumulation of senescent osteoblasts in the bone trabecula of PS-MPs treated mice, as well as the impaired autophagy with decreased autophagosome and reduced autophagy-related proteins in the senescent osteoblasts. Re-establishing autophagy effectively reversed the senescent phenotype in osteoblasts and ameliorated PS-MPs induced skeletal growth arrest. Hence, our study reveals the detrimental role of PS-MPs in skeletal growth in puberty through accelerating osteoblast senescence, which may be alleviated by reactivating the autophagy. This study provides new evidence of the PS-MPs on health threats and the potential therapeutic targets to reverse it. Graphical abstract: Image 1 Highlights: PS-MPs induce skeletal dysplasia with impaired trabecular microarchitecture. PS-MPs accelerate osteoblast senescence as the results of impaired autophagy. Targeting autophagy alleviates osteoblast senescence to redeem PS-MPs impaired skeletal growth.